Cytokines and VEGF Induction in Orthodontic Movement in Animal Models. (14th May 2012) - Di Domenico, M.; D'apuzzo, F.; Feola, A.; Cito, L.; Monsurrò, A.; Pierantoni, G. M.; Berrino, L.; De Rosa, A.; Polimeni, A.; Perillo, L.
Abstract : Orthodontics is a branch of dentistry that aims at the resolution of dental malocclusions. The specialist carries out the treatment using intraoral or extraoral orthodontic appliances that require forces of a given load level to obtain a tooth movement in a certain direction in dental arches. Orthodontic tooth movement is dependent on efficient remodeling of periodontal ligament and alveolar bone, correlated with several biological and mechanical responses of the tissues surrounding the teeth. A periodontal ligament placed under pressure will result in bone resorption whereas a periodontal ligament under tension results in bone formation. In the primary stage of the application of orthodontic forces, an acute inflammation occurs in periodontium. Several proinflammatory cytokines are produced by immune-competent cells migrating by means of dilated capillaries. In this paper we summarize, also through the utilization of animal models, the role of some of these molecules, namely, interleukin-1 β and vascular endothelial growth factor, that are some proliferation markers of osteoclasts and osteoblasts, and the macrophage colony stimulating factor.